Hydrogen sulfide‐loaded microbubbles combined with ultrasound mediate thrombolysis and simultaneously mitigate ischemia‐reperfusion injury in a rat hindlimb model - Zhong, Jiayuan (J Thromb Haemost, 2021)
BACKGROUND: Thromboembolism and subsequent ischemia/reperfusion injury (IRI) remain major clinical challenges. OBJECTIVES: To investigate whether hydrogen sulfide (H(2)S)‐loaded microbubbles (hs‐Mbs) combined with ultrasound (US) radiation (hs‐Mbs+US) dissolve thrombi and simultaneously alleviate tissue IRI through local H(2)S release. METHODS: hs‐Mbs were manufactured and US‐triggered H(2)S release was recorded. White and red thromboembolisms were established ex vivo and in rats left iliac artery. All subjects randomly received control, US, Mbs+US, or hs‐Mbs+US treatment for 30 minutes. RESULTS: H(2)S was released from hs‐Mbs+US both ex vivo and in vivo. Compared with control and US, hs‐Mbs+US and Mbs+US showed comparable substantial decreases in thrombotic area, clot mass, and flow velocity increases for both ex vivo macrothrombi. In vivo, hs‐Mbs+US and Mbs+US caused similarly increased recanalization rates, blood flow velocities, and hindlimb perfusion for both thrombi compared with the other treatments, with no obvious influence on hemodynamics, respiration, and macrophage vitality. More importantly, hs‐Mbs+US substantially alleviated skeletal muscle IRI by reducing reactive oxygen species, cellular apoptosis, and proapoptotic Bax, caspase‐3, and caspase‐9 and increasing antiapoptotic Bcl‐2 compared with other treatments. In vitro, hypoxia/reoxygenation‐predisposed skeletal muscle cells and endothelial cells treated with normal saline solution exhibited similar trends, which were largely reversed by an H(2)S scavenger or an inhibitor of Akt phosphorylation. CONCLUSION: hs‐Mbs+US effectively dissolved both white and red macrothrombi and simultaneously alleviated skeletal muscle IRI through the US‐triggered, organ‐specific release of H(2)S. This integrated therapeutic strategy holds promise for treating thromboembolic diseases and subsequent IRI.